Índios, jesuítas e bandeirantes no alto Jacuí : implicações históricas e geopolíticas da redução de Santa Teresa del Curiti - Vicroski, Fabrício José Nazzari (2018)
The Jesuit reduction of Santa Teresa del Curiti was founded in 1632 by Father Francisco Ximenez in the northwest region of the current state of Rio Grande do Sul. In the following year, the incipient settlement was transmigrated to a position further south. The new location allowed articulation with the other reductions and mitigated the risk of attacks by the Jê Indians. Both locations were located in the upper Jacuí basin, then called Igaí. It was a prosperous town with a strategic location. Its population exceeded four thousand people. Seduced by the lucrative slave trade, the bandeirantes from São Paulo threw themselves into the Tape missions. In 1637 a troop commanded by André Fernandes invaded the reduction of Santa Teresa. The indigenous people were captured and sent to São Paulo where they were sold as slaves. Fully aware of the strategic location of the reduction, the bandeirantes established a supply post there. For more than three decades, the site served as a support base for the Portuguese-Brazilian penetration towards the interior of the territory of Rio Grande do Sul, helping to take over the other missionary villages and also in military campaigns. From this base, the Paulistas launched attacks to the west, south and southwest. Just over three decades later, maintaining this important position became unsustainable. The interpretation of the historical facts related to the founding of the Santa Teresa reduction and the subsequent establishment of a support post for the bandeirantes attacks allows extrapolating the geographical limits of the Tape zone. The Igaí camp was consolidated as the radiating pole of the Luso-Brazilian slave explorers of Rio Grande do Sul in the 17th century. It is estimated that around 30,000 indigenous people were subjugated. The traditional settlement dynamics of the native populations was disrupted. The territorial dispute reached a new level. The regional clashes reflected the geopolitical context of the overseas powers. The issue envisioned is due to the forgetting of this past, rarely or superficially addressed. Through the development of this research, it is intended to highlight the historical importance of the listed facts, defending the thesis that the events resulting from the foundation of the reduction had profound historical and geopolitical implications in the formation of Rio Grande do Sul.